Management of elderly patients with chronic lymphocytic leukemia in the era of targeted therapies. Issue 5 (September 2015) - Ysebaert, Loïc; Feugier, Pierre; Michallet, Anne-Sophie
<x xml:space="preserve">Abstract</x> Purpose of review Chronic lymphocytic leukemia (CLL) is frequently diagnosed after 71 years, though median age in published clinical trials with standard chemoimmunotherapy regimens in frontline or relapse setting is mostly below 70 years (58–71 years). Development of oral, less toxic and thus more affordable targeted therapies offers new therapeutic options in those patients deemed unfit for chemotherapy. Recent findings This review will discuss results of these new agents in the therapy of elderly patients. Apart from discussing the impact of chronological age, creatinine clearance and cumulative illness rating scale scores in the clinical outcomes, we will also discuss how individualized treatment decision-making should include more precise geriatric assessment tools to thoroughly assess life expectancy, anticipate tolerability, to avoid deleterious stress precipitating prefrail patients into definitive loss of capacity, with dramatic social and economic costs. Summary In the era of new targeted agents to fight cancers, we propose concepts to help us understand how elderly dedicated trial designs and geriatric assessment tools (apart from the evaluation of CLL biological risk factors) will undoubtedly revolutionize therapeutic approaches in everyday practice CLL patients.